Anti-paćiw of Gadje academia, Ficowski’s shadow and what to do about it – exercises in reciprocal ethnography and decolonizing the Polish Romani studies - Fiałkowska, Kamila; Garapich, Michał P.; Jóźwiak, Ignacy; Mirga-Wójtowicz, Elżbieta; Styrkacz, Sonia; Szewczyk, Monika (Romano džaniben, 2023)
This article, authored by a group of Romani and non-Romani academics, examines the assumptions behind researching Romani communities in Poland. Current Romani studies in Poland are often limited by a colonial essentialist paradigm, perpetuating stereotypes and excluding Romani history from the broader Polish narrative. We argue that as knowledge production is still dominated by non-Romani scholars, this leads to a distorted and empirically misguided portrayals of the life of the Roma in Poland. To address this issue, we advocate for a participatory research approach involving Romani researchers, acknowledging the diverse voices within both Romani and non-Romani communities. This long-term process presents unique ethical and methodological challenges, but open discussion and challenging hierarchical nature of academic discourses is crucial for progress and creation of more inclusive, decolonized knowledge.